2022
DOI: 10.1152/ajpregu.00280.2021
|View full text |Cite
|
Sign up to set email alerts
|

Faster early rate of force development in warmer muscle: an in vivo exploration of fascicle dynamics and muscle-tendon mechanical properties

Abstract: While heat exposure has been shown to increase the rate of force development (RFD), the underlying processes remain unknown. This study investigated the effect of heat on gastrocnemius medialis (GM) muscle-tendon properties and interactions. Sixteen participants performed electrically-evoked and voluntary contractions combined with ultrafast ultrasound under thermoneutral (CON: 26°C, core temperature 37.0±0.3°C, muscle temperature 34.0±1.1°C) and passive heat exposure (HOT: 47°C, core temperature 38.4±0.3°C, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…Needless to say, the fascicle shortening velocity was not constant during isokinetic contractions (e.g., Ichinose et al, 2000 ). Unfortunately, it was impossible in this study to calculate the instantaneous maximal fascicle shortening velocity using an ultrafast ultrasonic device (2000 Hz) as in the previous studies (Beaumatin et al, 2017 ; Hauraix et al, 2015 , 2017 ; Mornas et al, 2022 ).…”
Section: Discussionmentioning
confidence: 90%
“…Needless to say, the fascicle shortening velocity was not constant during isokinetic contractions (e.g., Ichinose et al, 2000 ). Unfortunately, it was impossible in this study to calculate the instantaneous maximal fascicle shortening velocity using an ultrafast ultrasonic device (2000 Hz) as in the previous studies (Beaumatin et al, 2017 ; Hauraix et al, 2015 , 2017 ; Mornas et al, 2022 ).…”
Section: Discussionmentioning
confidence: 90%
“…Soft tissue stiffness, measured through passive GM and active Achilles tendon stiffness, was also unaffected from PRE to POST in the HA and CON groups. Although our recent study reported an acute decrease in passive GM muscle and active Achilles tendon stiffness at the end of a passive acute heat exposure (33), no study has yet reported the effects of active HA on soft tissue stiffness. These findings suggest that changes in tissue stiffness induced by acute heat exposure are transient and do not translate into chronic adaptations after repeated active HA sessions.…”
Section: Discussionmentioning
confidence: 91%
“…Of note, the effects described in the current study are resulting from testing performed in temperate environment, and it remains unclear how this absence of effects may affect, or not, the acute muscle–tendon unit properties responses to heat exposure during exercise, especially because we have recently demonstrated a modification of some of these properties (i.e., faster early RTD, rightward shift of the joint force–velocity relationship, and reduced soft tissue stiffness after an acute passive heat exposure [33]). An interesting perspective from this work would be to investigate the effects of an active HA on the acute responses of a low-intensity cycling session performed in hot and humid environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations